Starch-containing material and producing method thereof as well as method for improving transparency of starch-containing material for molding
By combining amorphous starch with organic acids, the physical properties of starch-containing materials are improved, addressing the limitations of existing starch materials and enhancing their mechanical strength and transparency for use in plastic substitutes.
Patent Information
- Application Number
- JP2023107783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Existing starch-containing materials lack desirable physical properties such as mechanical strength and transparency, limiting their use as plastic substitutes.
Incorporating amorphous starch and organic acids or their salts into the starch-containing materials, forming a chemical structure that modifies the starch to break hydrogen bonds, thereby improving mechanical properties and transparency.
The method enhances the mechanical properties and transparency of starch-containing materials, making them suitable for various applications including packaging and molded products.
Smart Images

Figure 2025006791000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a starch-containing material, particularly to a starch-containing material containing amorphous starch. The present invention also relates to a method for improving the transparency of a starch-containing material for molding, particularly to a method for improving the transparency of a starch-containing material for molding by using amorphous starch. [Background technology]
[0002] In recent years, mass production and mass consumption of plastics have become a problem. Since plastics do not decompose in nature, they become microplastics when they drift in the ocean, becoming unrecoverable man-made objects and polluting the environment. For this reason, various proposals have been made for alternative materials to plastics. For example, Patent Document 1 below discloses a starch composite material containing low-crystalline starch and glycerin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-187956 Summary of the Invention [Problem to be solved by the invention]
[0004] It is considered important to improve the physical properties of plastic alternative materials in order to make the plastic alternative materials more widely used. Starch-containing materials are promising as plastic alternative materials, and improvement of the physical properties is considered to contribute to increasing the usefulness of starch-containing materials. Therefore, the present invention aims to improve the physical properties of starch-containing materials, particularly to improve the mechanical properties or transparency. [Means for solving the problem]
[0005] The present inventors have found that by employing a specific configuration, the physical properties of a starch-containing material can be improved.
[0006] That is, the present invention provides the following. [1] Amorphous starch, an organic acid, a salt of an organic acid, or both; A starch-containing material comprising: [2] The starch-containing material according to [1], wherein the organic acid is a hydroxycarboxylic acid. [3] The starch-containing material according to [1] or [2], wherein the organic acid has one or more hydroxyl groups. [4] The starch-containing material according to any one of [1] to [3], wherein the organic acid includes one or a combination of two or more selected from the group consisting of citric acid, malic acid, tartaric acid, and lactic acid. [5] The starch-containing material according to any one of [1] to [4], wherein the amorphous starch has a chemical structure formed by a reaction between a hydroxy group of the amorphous starch and the organic acid or a salt of the organic acid. [6] The starch-containing material according to any one of [1] to [5], which is a dried reaction product of the amorphous starch and the organic acid or a salt of the organic acid. [7] The starch-containing material according to any one of [1] to [6], wherein the amorphous starch has a crystallinity of 20% or less. [8] The starch-containing material according to any one of [1] to [7], further comprising one or more components selected from the group consisting of polyhydric alcohols, polysaccharides, and sugars. [9] The starch-containing material according to any one of [1] to [8], wherein the polyhydric alcohol includes one or a combination of two or more selected from the group consisting of glycerin, sorbitol, maltitol and erythritol.
[10] The starch-containing material according to any one of [1] to [9], further comprising a thermoplastic resin.
[11] When the starch-containing material was subjected to FT-IR measurement, -1 ~1750cm -1 The starch-containing material according to any one of [1] to
[10] , which exhibits a peak at
[12] The starch-containing material according to any one of [1] to
[11] , which has moldability such that the starch-containing material can be molded into a 5B type dumbbell test piece in accordance with JIS K 7161-2 by hot pressing at 120°C.
[13] Providing an amorphous starch; and mixing the amorphous starch with an organic acid, a salt of an organic acid, or both; The present invention relates to a method for producing a starch-containing material containing amorphous starch and an organic acid, a salt of an organic acid, or both of these, comprising the steps of:
[14] The method according to
[13] , wherein the amorphous starch is contacted with the organic acid, the salt of the organic acid, or both of them in a solvent.
[15] A method for producing a starch-containing material for molding using amorphous starch, A method for improving the transparency of starch-containing materials for molding.
[16] The method according to
[15] , which suppresses an increase in crystallinity in the starch-containing material for molding.
[17] The method according to
[15] or
[16] , wherein starch recrystallization is suppressed when the starch-containing material for molding is molded.
[18] The method according to any one of
[15] to
[17] , wherein the starch-containing material for molding is prevented from recrystallizing during storage at room temperature. Effect of the Invention
[0007] The present invention can improve the physical properties of starch-containing materials. For example, the present invention can improve the mechanical properties of starch-containing materials. Also, the present invention can improve the transparency of starch-containing materials. The effects of the present invention are not necessarily limited to the effects described herein, and may be any of the effects described in this specification. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a schematic diagram of a mortar-type grinding device. [Diagram 2]FIG. 1 is a diagram showing the results of wide-angle X-ray diffraction measurement. [Figure 3A] FIG. 2 is a schematic diagram for explaining a method for producing a starch-containing material. [Figure 3B] FIG. 1 shows photographs of the four types of starch prepared. [Figure 4] FIG. 1 shows the results of FT-IR measurement. [Diagram 5] FIG. 2 is a schematic diagram for explaining a dumbbell-shaped test piece. [Figure 6] FIG. 2 is a photograph of a starch-containing material before and after compression molding. [Figure 7] FIG. 13 shows the results of a tensile test. [Figure 8] FIG. 2 is a schematic diagram for explaining the improvement of the mobility of starch molecular chains. [Figure 9] FIG. 1 is a diagram showing the results of wide-angle X-ray diffraction measurement. [Figure 10] FIG. 13 is a diagram showing the results of transmittance measurement. [Figure 11] FIG. 1 is a diagram showing the results of wide-angle X-ray diffraction measurement, and a schematic diagram for explaining starch amorphization by kneading and starch recrystallization by molding. [Figure 12] FIG. 1 shows the results of wide-angle X-ray diffraction measurement, and is a schematic diagram for explaining the inhibition of starch recrystallization. [Figure 13] FIG. 1 is a diagram showing the results of wide-angle X-ray diffraction measurement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, the embodiments of the present invention will be described in detail. The description of the present invention will be given in the following order. 1. Starch-containing materials 1.1 Amorphous starch 1.2 Organic acids 1.3 Plasticizers such as polyhydric alcohols, polysaccharides, and sugars 1.4 Thermoplastic resin 1.5 Physical Properties 1.6 Manufacturing method 1.7 Application 2. Method for improving transparency of starch-containing materials for molding 3. Working Example 3.1 Tests on combinations of amorphous starch and organic acids 3.1.1 Preparation of amorphous starch 3.1.2 Preparation of citric acid-modified starch and confirmation of modification 3.1.3 Preparation and evaluation of thermoplastic starch-containing materials 3.2 Testing for improving transparency by amorphous starch 3.2.1 Preparation of amorphous starch 3.2.2 Preparation and evaluation of starch-containing materials 3.2.3 Effect of storage at room temperature on crystallinity The embodiments described below are representative examples of the present invention, and the present invention is not limited to these embodiments.
[0010] 1. Starch-containing materials
[0011] The starch-containing material of the present invention contains amorphous starch and an organic acid, an organic acid salt, or both of these. The starch-containing material of the present invention exhibits excellent physical properties, particularly excellent mechanical properties, due to the combination of amorphous starch and an organic acid, an organic acid salt, or both of these. Preferably, the amorphous starch may be modified with the organic acid, the organic acid salt, or both of these, and it is believed that the modification particularly contributes to the exhibiting of excellent physical properties.
[0012] The composition of the starch-containing material of the present invention is described in more detail below.
[0013] 1.1 Amorphous starch The starch-containing material of the present invention contains amorphous starch (also called α-starch). The amorphous starch means starch having a lower degree of crystallinity compared to crystalline starch (also called β-starch). The degree of crystallinity of the amorphous starch may be, for example, 50% or less, preferably 40% or less, more preferably 30% or less, even more preferably 20% or less, particularly preferably 15% or less, and even 10% or less.
[0014] The degree of crystallinity of amorphous starch can be appropriately controlled by adjusting the grinding conditions in the manufacturing method of amorphous starch described below. The degree of crystallinity of starch is calculated by any known technique. The degree of crystallinity of starch is determined based on the results of X-ray diffraction intensity. Specifically, a peak representing an amorphous portion and a peak representing a crystalline portion are extracted from the results of X-ray diffraction intensity. A known peak separation technique is used arbitrarily to extract each peak. Although multiple peaks representing crystalline portions can be extracted, only multiple peaks whose peak values exceed a predetermined value are used to determine the degree of crystallinity. Then, the degree of crystallinity is determined from the ratio of the peak representing the amorphous portion to the peak representing the crystalline portion. For example, the crystallinity is calculated by inserting the area A of the peak representing the crystalline portion (the total value of the areas of multiple peaks) and the area B of the peak representing the amorphous portion into the following formula (1). Crystallinity (%) = 100 x Area A / (Area A + Area B)…(1) The peak angle used in formula (1) is adjusted appropriately depending on the raw material and the grinding method used when grinding the raw material.
[0015] Amorphous starch is produced from a plant raw material such as a grain or pseudo-cereal containing starch as a main component. Examples of the plant raw material include rice, potato, wheat, soybean, red bean, buckwheat, potatoes, beans, and corn. Amorphous starch may be produced from crystalline starch produced from these plant raw materials. For example, tapioca produced from cassava roots may be used as the raw material. The type of amorphous starch used in the present invention may be appropriately changed depending on the type of raw material. For example, one containing either one or both of amylose and amylopectin is exemplified as an amorphous starch.
[0016] The amorphous starch may be produced by a production method known in the art, for example, the production method described in JP 2007-75104 A, JP 2010-215861 A, or JP 2009-213472 A.
[0017] In a preferred embodiment, the amorphous starch may be an amorphous starch produced by grinding starch (e.g., crystalline starch) using a milling machine, particularly a temperature-controlled milling machine, such as the machine described in the following examples. The grinding temperature in the grinding treatment may be, for example, 80° C. or higher, preferably 90° C. or higher, and more preferably 100° C. or higher. The grinding temperature may be, for example, 200° C. or lower, preferably 180° C. or lower, more preferably 160° C. or lower, and may be, for example, 140° C. or lower. Amorphous starch is produced by grinding starch (e.g., crystalline starch) under shear conditions while heating it at this temperature. That is, amorphous starch may be produced by performing a grinding treatment on starch (e.g., crystalline starch) in which heating and shearing are performed simultaneously. The inter-mill distance (the distance between the upper and lower mills) of the mortar-type milling device in the milling process may be, for example, 10 μm or less, preferably 8 μm or less, more preferably 6 μm or less, particularly preferably 4 μm or less, and further preferably 2 μm or less, for example, 0 μm. Milling starch by operating the mortar-type milling device at such an inter-mill distance contributes to obtaining amorphous starch suitable for achieving the effects of the present invention. The rotation speed of the mill in the grinding process (the rotation speed of one mill relative to the other mill) may be, for example, 200 rpm or less, preferably 150 rpm or less, more preferably 100 rpm or less. The rotation speed of the mill may be, for example, 10 rpm or more, preferably 20 rpm or more, more preferably 30 rpm or more. Such a rotation speed can contribute to appropriate temperature control. In addition, such a rotation speed contributes to obtaining amorphous starch suitable for achieving the effects of the present invention.
[0018] In a preferred embodiment, water may not be added in the milling process. In order to decrystallize starch, it is generally necessary to add water and then heat the starch, but the above-mentioned milling process may be carried out without adding water to the starch, i.e., amorphous starch can be obtained without adding water. The addition of water results in excess water being present in the starch-containing material being produced, which can adversely affect the physical properties of the molding material, for example reducing dimensional stability. The amorphous starch obtained by the grinding treatment without adding water as described above does not contain excess water, which contributes to obtaining a molding material with excellent physical properties. The amorphous starch produced in this manner is particularly suitable for achieving the effects of the present invention.
[0019] The amorphous starch may preferably have a chemical structure formed by the reaction of a hydroxy group of the amorphous starch with an organic acid, an organic acid salt, or both of these described below. That is, the amorphous starch may be modified with an organic acid, an organic acid salt, or both of these described below. The modification may be a modification that eliminates hydrogen bonds between starch molecular chains, particularly hydrogen bonds between amylopectin chains. The modification contributes to imparting desirable physical properties (e.g., mechanical properties) to the starch-containing material.
[0020] The content of the amorphous starch in the starch-containing material of the present invention may be, for example, 30% by mass or more, particularly 40% by mass or more, more particularly 50% by mass or more, and may even be 60% by mass or more, 70% by mass or more, or 80% by mass or more, relative to the mass of the starch-containing material of the present invention. The content of the amorphous starch in the starch-containing material of the present invention may be, for example, 90% by mass or less, particularly 80% by mass or less, and more particularly 70% by mass or less, based on the mass of the starch-containing material of the present invention. By using such a content ratio, the physical property improving effect due to the combination of the amorphous starch and the organic acid is more effectively exhibited.
[0021] 1.2 Organic acids The starch-containing material of the present invention contains an organic acid, a salt of an organic acid, or both, which is believed to contribute to the favorable physical properties of the starch-containing material by breaking hydrogen bonds between starch molecular chains, particularly hydrogen bonds between amylopectin chains, due to the organic acid or its salt. Preferably, the amorphous starch has a chemical structure formed by a reaction between a hydroxy group of the amorphous starch and the organic acid, a salt of the organic acid, or both of them. That is, the amorphous starch may be modified with the organic acid or the salt thereof. It is believed that the modification causes the elimination of hydrogen bonds as described above.
[0022] 1.2.1 Types of organic acids The organic acid may be an organic acid having one or more carbon atoms, and in particular may be an organic acid having two or more carbon atoms. In one preferred embodiment, the organic acid may be a low molecular weight organic acid, for example, an organic acid having 10 or less carbon atoms, preferably an organic acid having 8 or less carbon atoms, more preferably an organic acid having 6 or less carbon atoms. A low molecular weight organic acid is considered to be preferable for the above-mentioned dissolution of hydrogen bonds. For example, a low molecular weight leads to a small number of hydroxyl groups in the organic acid. In order to dissolve hydrogen bonds, it is better to have a small number of hydroxyl groups. In another preferred embodiment, the organic acid may be a high molecular weight organic acid, for example an organic acid having more than 10 carbon atoms, preferably an organic acid having 12 or more carbon atoms, and more preferably an organic acid having 14 or less carbon atoms. The number of carbon atoms means the number of carbon atoms contained in one molecule of the organic acid, and in particular may mean the number of carbon atoms in the chemical formula of the organic acid.
[0023] The salt of the organic acid may be, for example, an alkali metal salt or an alkaline earth metal salt. The alkali metal salt may be a lithium salt, a sodium salt, or a potassium salt. The alkaline earth metal salt may be a magnesium salt or a calcium salt. The salt of the organic acid may be a salt in which a characteristic group exhibiting characteristics of an acid, such as a carboxy group, is partially neutralized and partially unneutralized. It is believed that the unneutralized characteristic group is particularly useful for the modification of amorphous starch.
[0024] The organic acid may be an organic acid having one or more carboxy groups. The organic acid may be, for example, a hydroxycarboxylic acid, a fatty acid, or a dicarboxylic acid, or a combination of two or more of these. The characteristic group that gives the organic acid an acidic characteristic may be a carboxy group, a hydroxy group, an enol group, or a thiol group. That is, the organic acid may be an organic acid having a carboxy group, a hydroxy group, an enol group, or a thiol group as a characteristic group of the acid. More specific examples of these organic acids are as described below, and the organic acid contained in the starch-containing material of the present invention may be one of these or a combination of two or more of them.
[0025] In a preferred embodiment, the organic acid is preferably a hydroxycarboxylic acid, which contributes to breaking up the hydrogen bonds between the amylopectin chains of starch. The hydroxycarboxylic acid may have one or more hydroxy groups, for example 1, 2, 3, 4 or 5 hydroxy groups, preferably 1, 2 or 3 hydroxy groups. The hydroxy group (-OH) is not a hydroxy group in a carboxy group (-COOH). The hydroxycarboxylic acid may have one or more carboxy groups, for example 1, 2, 3, 4 or 5 carboxy groups, preferably 1, 2 or 3 carboxy groups. The hydroxycarboxylic acid has, for example, 10 or less carbon atoms, preferably 8 or less carbon atoms, and more preferably is an organic acid having 6 or less carbon atoms.
[0026] Examples of hydroxycarboxylic acids include glycolic acid, lactic acid, tartronic acid, glyceric acid, hydroxybutyric acid (especially 2-hydroxybutyric acid, 3-hydroxybutyric acid, and gamma-hydroxybutyric acid), malic acid, tartaric acid, citramalic acid, citric acid, and isocitric acid. Preferably, the organic acid comprises one or a combination of two or more of citric acid, malic acid, tartaric acid, and lactic acid, and in particular, the organic acid is one or a combination of two or more of citric acid, malic acid, tartaric acid, and lactic acid.
[0027] In another preferred embodiment, the organic acid is preferably a fatty acid, which is believed to contribute to breaking up the hydrogen bonds between the amylopectin chains of starch. The fatty acid may be a saturated fatty acid or an unsaturated fatty acid. The fatty acid may be, for example, a short chain fatty acid (particularly a fatty acid having 2, 4 or 6 carbon atoms), a medium chain fatty acid (particularly a fatty acid having 8 or 10 carbon atoms), or a long chain fatty acid (particularly a fatty acid having 12, 14, 16, 18, 20, 22 or 24 carbon atoms), and in particular a short chain fatty acid or a medium chain fatty acid may be used as the organic acid. One or a combination of two or more of these may be used as the organic acid. Examples of the fatty acid include acetic acid, butyric acid, caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, or linolenic acid, one or a combination of two or more of which may be used as the organic acid.
[0028] In yet another preferred embodiment, the organic acid is a dicarboxylic acid, which is believed to contribute to breaking up hydrogen bonds between the amylopectin chains of starch. Examples of the dicarboxylic acid include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid, one or more of which may be used as the organic acid.
[0029] 1.2.2 Modification of amorphous starch with organic acids The organic acid, the salt of the organic acid, or both (hereinafter collectively referred to as "organic acid compound") may be used to modify the amorphous starch. In particular, as described above, the organic acid compound may modify the amorphous starch so as to break hydrogen bonds between starch molecular chains of the amorphous starch. That is, in the starch-containing material of the present invention, the amorphous starch may have a chemical structure formed by a reaction between a hydroxy group of the amorphous starch and the organic acid compound, and the amorphous starch may be modified by the reaction.
[0030] To carry out the modification, the organic acid compound may be contacted with the amorphous starch in a state where it is dissolved in a predetermined solvent, which is preferably a solvent other than water, and may be, for example, an organic solvent that does not contain water. If water is present during the contact between the organic acid compound and the amorphous starch, water may be present in the starch-containing material produced. As mentioned above, water may adversely affect the physical properties of the molding material, for example, the dimensional stability may be deteriorated. Therefore, it is desirable that the contact is carried out in a solvent that is free of water. It is believed that the reaction between the organic acid compound and the amorphous starch in a water-free solvent contributes to the resulting reaction product (i.e., organic acid-modified amorphous starch) acquiring physical properties that are desirable for molding.
[0031] The solvent is preferably a solvent capable of dissolving an organic acid compound, and such a solvent can be appropriately selected by a person skilled in the art. In addition, the solvent is preferably a solvent that is easily volatile, so that the solvent can be easily removed after the modification of the amorphous starch with the organic acid. The solvent may be an organic solvent. The solvent may be, for example, a polar solvent, particularly a protic solvent. The type of the solvent may be selected according to the type of organic acid compound used, and may be appropriately selected from solvents that can dissolve the organic acid compound.
[0032] Examples of the polar solvent include, for example, alcohol solvents. Preferred examples of the alcohol solvent include methanol, ethanol (undenatured ethanol or denatured ethanol), isopropyl alcohol, and normal propyl alcohol, and one or a mixture of two or more of these may be used as the solvent.
[0033] In order to modify the amorphous starch with the organic acid compound, the organic acid compound is dissolved in the solvent to prepare an organic acid solution, which may be suitably carried out by a method known in the art.
[0034] Next, the amorphous starch is further mixed into the organic acid solution. In order to promote the denaturation, the organic acid solution may be maintained at a temperature of, for example, 30° C. or higher, preferably 40° C. or higher, more preferably 50° C. or higher, and even more preferably 60° C. or higher. In addition, the temperature may be maintained at, for example, 100° C. or lower, preferably 90° C. or lower, in order to prevent the solvent from volatilizing. At such a temperature, the solution to which the amorphous starch has been added may be stirred for, for example, 1 hour or more, preferably 5 hours or more, further 10 hours or more, 15 hours or more, or 20 hours or more. The upper limit of the stirring time does not need to be particularly limited, but may be, for example, 50 hours or less, 45 hours or less, or 40 hours or less, from the viewpoint of, for example, the volatility of the solvent. In this manner, the starch is modified by the organic acid compound within the solution.
[0035] Next, the organic acid solution mixed with the amorphous starch may be optionally subjected to a washing treatment such as suction filtration washing. The washing may remove, for example, a solvent. The reaction product after the washing treatment (for example, the residue in the case of filtration washing) is dried to obtain amorphous starch modified with an organic acid compound. The method of the drying treatment may be appropriately selected by a person skilled in the art so as not to adversely affect the reaction product (for example, to prevent coloring of the starch). For example, the drying process may be a vacuum drying process. The vacuum drying process may be carried out at, for example, 10° C. or higher, preferably 20° C. or higher, more preferably 30° C. or higher, or even 40° C. or higher for efficient drying. The vacuum drying process may be carried out at, for example, 80° C. or lower, preferably 70° C. or lower, more preferably 60° C. or lower, for example, to prevent discoloration of starch. The vacuum drying treatment may be carried out until the solvent is removed, for example, for 1 hour or more, preferably 5 hours or more, and even 10 hours or more, and may be carried out for, for example, 50 hours or less, 40 hours or less, or 30 hours or less. The solvent is removed in the manner described above to obtain amorphous starch modified with an organic acid compound. The obtained amorphous starch is, for example, in a dried state, and may be, for example, in a solid form, particularly in a powder or granular form, more particularly in a powder form. That is, the starch-containing material of the present invention may include a dried product of the reaction between the amorphous starch and the organic acid compound.
[0036] The mixing ratio of the amorphous starch and the organic acid compound used in the reaction may be appropriately adjusted depending on factors such as the type of the organic acid compound. The organic acid compound and the amorphous starch may be mixed in an amount of, for example, 5 parts by mass or more, preferably 60 parts by mass or more, and more preferably 120 parts by mass or more per 100 parts by mass of the amorphous starch. Furthermore, the organic acid compound and the amorphous starch may be mixed so that the organic acid compound is, for example, 360 parts by mass or less, preferably 300 parts by mass or less, and more preferably 240 parts by mass or less per 100 parts by mass of the amorphous starch. That is, the starch-containing material of the present invention may contain the amorphous starch and the organic acid compound in such a ratio.
[0037] The total content of the amorphous starch and the organic acid compound in the starch-containing material of the present invention may be, for example, 30% by mass or more, particularly 40% by mass or more, more particularly 50% by mass or more, and may even be 60% by mass or more, 70% by mass or more, or 80% by mass or more, relative to the mass of the starch-containing material of the present invention. The total content of the amorphous starch and the organic acid compound in the starch-containing material of the present invention may be, for example, 90% by mass or less, particularly 80% by mass or less, and more particularly 70% by mass or less, relative to the starch-containing material of the present invention. The above numerical range of the total content may be applied, for example, when the starch-containing material of the present invention does not contain a thermoplastic resin, but may also be applied when the starch-containing material contains a thermoplastic resin. In some embodiments, such as when the starch-containing material of the present invention contains a thermoplastic resin, the total content of the amorphous starch and the organic acid compound in the starch-containing material may be even lower, for example, the total content may be 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less. In addition, the total content may be, for example, 1% by mass or more, 2% by mass or more, or 3% by mass or more. In this way, a lower total content may be adopted depending on the content of the thermoplastic resin.
[0038] 1.3 Plasticizers such as polyhydric alcohols, polysaccharides, and sugars The starch-containing material of the present invention may further contain a plasticizer in addition to the amorphous starch and the organic acid compound. The plasticizer enhances the moldability of the starch-containing material. That is, the present invention also provides a starch-containing material for molding. The starch-containing material for molding contains amorphous starch, an organic acid compound, and a plasticizer. The starch-containing material may contain the plasticizer in an amount of, for example, 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, 25% by mass or more, or 30% by mass or more, based on the mass of the starch-containing material. The starch-containing material may contain the plasticizer in an amount of, for example, 55% by mass or less, preferably 50% by mass or less, more preferably 45% by mass or less or 40% by mass or less, based on the mass of the starch-containing material. The above range of the content of the plasticizer may be applied, for example, when the starch-containing material of the present invention does not contain a thermoplastic resin, but may also be applied when the starch-containing material contains a thermoplastic resin. In some embodiments, such as when the starch-containing material of the present invention contains a thermoplastic resin, the content of the plasticizer in the starch-containing material may be even lower, for example, the content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less. In addition, the content may be, for example, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more.
[0039] Examples of the plasticizer include polyhydric alcohols, polysaccharides, and sugars. Here, the polysaccharides are not starch, i.e., polysaccharides other than starch. Also, the sugars are not starch and not polysaccharides, i.e., sugars other than starch and polysaccharides. In other words, the sugars are monosaccharides, disaccharides, oligosaccharides, and sugar alcohols. In addition, the plasticizer is not water, i.e., in this specification, the plasticizer means a plasticizer other than water.
[0040] The polyhydric alcohol refers to an alcohol having two or more hydroxyl groups in the molecule. The polyhydric alcohol is preferably a polyhydric alcohol having 2 to 5 carbon atoms, more preferably a polyhydric alcohol having 2 to 4 carbon atoms. The polyhydric alcohol preferably has 2 to 5 hydroxyl groups (OH groups), more preferably has 2 to 4 hydroxyl groups (OH groups). The polyhydric alcohol may include, for example, glycerin and glycol. Examples of the glycol include ethylene glycol, propylene glycol, and 1,3-butylene glycol. That is, the polyhydric alcohol may preferably include one or a combination of two or more selected from glycerin, ethylene glycol, propylene glycol, and 1,3-butylene glycol. Particularly preferably, the polyhydric alcohol is glycerin. The starch-containing material may contain the polyhydric alcohol in a content of, for example, 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, 25% by mass or more, or 30% by mass or more, relative to the mass of the starch-containing material. The starch-containing material may contain the polyhydric alcohol in an amount of, for example, 55% by mass or less, preferably 50% by mass or less, more preferably 45% by mass or less or 40% by mass or less, based on the mass of the starch-containing material. Such a content ratio can impart physical properties suitable for use as a molding material to the starch-containing material. The above range of the content of the polyhydric alcohol may be applied, for example, when the starch-containing material of the present invention does not contain a thermoplastic resin, but may also be applied when the starch-containing material contains a thermoplastic resin. In some embodiments, such as when the starch-containing material of the present invention contains a thermoplastic resin, the content of the polyhydric alcohol in the starch-containing material may be even lower, for example, the content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less. In addition, the content may be, for example, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more.
[0041] Examples of the polysaccharides include glucomannan, curdlan, pullulan, paramylon, and alginic acid. Among the saccharides, examples of monosaccharides include glucose, galactose, and fructose. Among the sugars, disaccharides include, for example, sucrose, lactose, maltose, and trehalose. Among the saccharides, examples of oligosaccharides include fructooligosaccharides and galactooligosaccharides. Among the sugars, sugar alcohols include, for example, sorbitol, maltitol, and erythritol. The plasticizer may be any one or a combination of two or more of these polysaccharides and / or sugars. The starch-containing material may contain the polysaccharides and / or sugars in a content of, for example, 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, 25% by mass or more, or 30% by mass or more, relative to the mass of the starch-containing material. The starch-containing material may contain the polysaccharides and / or sugars in a content of, for example, 55% by mass or less, preferably 50% by mass or less, more preferably 45% by mass or less or 40% by mass or less, relative to the mass of the starch-containing material. The above ranges of the content of polysaccharides and / or sugars may be applied, for example, when the starch-containing material of the present invention does not contain a thermoplastic resin, but may also be applied when the starch-containing material contains a thermoplastic resin. In some embodiments, such as when the starch-containing material of the present invention contains a thermoplastic resin, the content of the polysaccharides and / or sugars in the starch-containing material may be even lower, for example, the content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less. In addition, the content may be, for example, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more.
[0042] Preferably, the starch-containing material may comprise one or a combination of two or more selected from the group consisting of glycerin, sorbitol, maltitol, and erythritol, which are particularly suitable for imparting desirable physical or moldable properties to the starch-containing material. The total content of glycerin, sorbitol, maltitol, and erythritol may be, for example, 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, 25% by mass or more, or 30% by mass or more, based on the mass of the starch-containing material. The total content of glycerin, sorbitol, maltitol, and erythritol may be, for example, 55% by mass or less, preferably 50% by mass or less, and more preferably 45% by mass or less or 40% by mass or less, based on the mass of the starch-containing material. The above numerical ranges of the total content of glycerin, sorbitol, maltitol, and erythritol may be applied, for example, when the starch-containing material of the present invention does not contain a thermoplastic resin, but may also be applied when the starch-containing material contains a thermoplastic resin. In some embodiments, such as when the starch-containing material of the present invention contains a thermoplastic resin, the total content in the starch-containing material may be even lower, for example, the total content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less. In addition, the total content may be, for example, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more.
[0043] Particularly preferably, the starch-containing material comprises glycerin, which is particularly suitable for imparting desirable physical or moldable properties to the starch-containing material. The glycerin content may be, for example, 10% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, 25% by mass or more, or 30% by mass or more, based on the mass of the starch-containing material. The glycerin content may be, for example, 55% by mass or less, preferably 50% by mass or less, and more preferably 45% by mass or less or 40% by mass or less, based on the mass of the starch-containing material. The above numerical range of the glycerin content may be applied, for example, when the starch-containing material of the present invention does not contain a thermoplastic resin, but may also be applied when the starch-containing material contains a thermoplastic resin. In some embodiments, such as when the starch-containing material of the present invention contains a thermoplastic resin, the glycerin content in the starch-containing material may be even lower, for example, the content may be 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, or 5% by mass or less. In addition, the content may be, for example, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more.
[0044] 1.4 Thermoplastic resin The starch-containing material may further include a thermoplastic resin. The thermoplastic resin may include at least a polyester-based resin or a polyolefin-based resin. That is, the starch-containing material according to the present invention may include a polyester-based resin or a polyolefin-based resin, or may include both of them. The thermoplastic resin may also be a polystyrene-based resin.
[0045] The content ratio of the thermoplastic resin is not particularly limited and may be appropriately selected by a person skilled in the art depending on, for example, the physical properties required of the starch-containing material. The starch-containing material may contain the thermoplastic resin in a proportion of, for example, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, or 30% by weight or less, based on the weight of the starch-containing material. The starch-containing material may contain the thermoplastic resin in an amount of, for example, 1% by mass or more, 5% by mass or more, or 10% by mass or more relative to the mass of the composition.
[0046] The polyolefin resin may be a polymer obtained by polymerization of olefins (e.g., α-olefins) as a main monomer. The polyolefin resin may be, for example, a polyethylene (PE) resin, a polypropylene (PP) resin, or a combination thereof.
[0047] The polyethylene resin may be, for example, an ethylene copolymer such as a low density polyethylene resin (LDPE: Low Density Polyethylene), a high density polyethylene resin (HDPE: High Density Polyethylene), a very low density polyethylene resin (VLDPE: Very Low Density Polyethylene), a linear low density polyethylene resin (LLDPE: Linear Low Density Polyethylene), an ethylene-vinyl acetate copolymer (EVA resin), or an ultra high molecular weight polyethylene resin (UHMW-PE: Ultra High Molecular Weight-Polyethylene), or a combination thereof.
[0048] The polyolefin resin may be preferably a biomass-derived polyolefin resin (e.g., biomass-derived polyethylene resin, etc.), and may be, for example, a biomass polyethylene resin. The biomass polyethylene resin may be, for example, LDPE, LLDPE, or HDPE. This can reduce CO2 emissions.
[0049] The polyolefin resin may be a metallocene-catalyzed polyolefin resin, i.e., the thermoplastic resin may be, for example, a metallocene-catalyzed polyethylene resin or polypropylene resin, or a combination thereof. The polystyrene-based resin may be a metallocene-catalyzed polystyrene-based resin.
[0050] The polyester resin may be a polymer in which monomers are polymerized through ester bonds. The polyester resin may be, for example, polyethylene terephthalate resin (PET), polyethylene naphthalate resin (PEN), polybutylene terephthalate resin (PBT), polylactic acid resin (PLA), polycarbonate resin (PC), polybutylene adipate terephthalate resin (PBAT), polybutylene succinate resin (PBS), polyhydroxyalkanoate resin (PHA), or a combination of two or more of these. In a preferred embodiment, the polyester resin may include PLA or PBAT, or a combination of these.
[0051] The polystyrene resin may be a polymer formed by polymerization of a styrene monomer. The polystyrene resin may be, for example, polystyrene resin, rubber-reinforced polystyrene resin (high impact polystyrene resin, HIPS), acrylonitrile-styrene copolymer (AS resin), methacrylate ester-styrene copolymer, acrylonitrile-acrylic rubber-styrene copolymer, acrylonitrile-ethylene propylene-styrene copolymer, or a combination of two or more of these.
[0052] The melting point of the thermoplastic resin is preferably 150° C. or less, more preferably 140° C. or less. By using a thermoplastic resin having a lower melting point, the molding temperature can be lowered, thereby preventing discoloration of the starch-containing material. The melting point of the thermoplastic resin may be, for example, 90° C. or higher, and more preferably 95° C. or higher. As used herein, the term "thermoplastic resin" does not include thermoplastic starches, such as amorphous starches. The term "thermoplastic resin" refers to a polymer that does not contain starch.
[0053] 1.5 Physical Properties The starch-containing material may have the physical property of being moldable by heating, i.e., the starch-containing material may be a material that can be molded into a desired shape in a heated state to form a molded article having the desired shape.
[0054] The molding method may be appropriately selected by those skilled in the art. For example, it may be press molding, compression molding, cast molding, vacuum molding, pressure molding, extrusion molding, injection molding, or blow molding. In addition, the composition of the starch-containing material may be appropriately adjusted depending on the molding method.
[0055] The starch-containing material may be a material having moldability that allows it to be molded into a 5B type dumbbell test piece conforming to JIS K 7161-2 by hot pressing at 120° C. The dumbbell test piece may have physical properties that allow a measured value of breaking strain to be obtained in a tensile test described below. The combination of amorphous starch and an organic acid compound allows the starch-containing material to be configured as a moldable material that can be molded into such test pieces.
[0056] When the starch-containing material is subjected to FT-IR measurement, -1 ~1750cm -1 The peak may be a peak derived from a carbonyl group of an organic acid compound, and the presence of this peak means that the amorphous starch has been modified by the organic acid compound.
[0057] The starch-containing material of the present invention may be a thermoplastic material, for example configured as a material that plasticizes at a temperature of 70°C or more, 90°C or more, 100°C or more, or 110°C or more. Furthermore, the upper limit of the temperature for plasticizing the starch-containing material is not particularly specified, but may be, for example, 200° C. or less, 150° C. or less, 140° C. or less, or 130° C. or less in order to prevent discoloration of the material. The starch-containing material may be used for molding at such temperatures.
[0058] 1.6 Manufacturing method The starch-containing material of the present invention may be produced by the production method described below. That is, the present invention also provides a production method for a starch-containing material containing amorphous starch and an organic acid compound.
[0059] The method may include the steps of preparing amorphous starch and mixing the amorphous starch with an organic acid compound. The mixture thus obtained may itself be used as the starch-containing material of the present invention, for example, by mixing with a plasticizer and using it for molding.
[0060] In the step of preparing the amorphous starch, the amorphous starch may be prepared as described in 1.1 above, or a pre-prepared amorphous starch may be prepared. The amorphous starch may be prepared by grinding starch (e.g., crystalline starch) as described in 1.1 above. Water may not be used in the grinding process. The grinding process may be carried out without adding water to the starch, and in particular, the grinding process may be carried out in the absence of water using the mortar-type grinding device described in 1.1 above. This allows the amorphous starch to be obtained without using water.
[0061] The type of organic acid compound used in the step of mixing the amorphous starch with the organic acid compound may be as described in 1.2.1 above. The step of mixing the amorphous starch with the organic acid compound may be carried out as described in 1.2.2 above, i.e., such that the amorphous starch is modified by the organic acid compound. The mixing may be carried out in the solvent (particularly a solvent not containing water) mentioned in 1.2.2 above. That is, the modification may be carried out by first dissolving the organic acid compound in the solvent to obtain an organic acid solution, and then mixing the amorphous starch into the organic acid solution. After the modification, washing is optionally carried out, and then the organic acid solution mixed with the amorphous starch (particularly the amorphous starch in the organic acid solution, for example the residue obtained by filtering the organic acid solution) is subjected to a drying treatment. The product obtained by the drying may be used as the starch-containing material of the present invention. That is, the starch-containing material may be the amorphous starch itself modified by the organic acid compound.
[0062] The method for producing a starch-containing material of the present invention may further include a step of mixing a plasticizer with the product. The plasticizer may be as described in 1.3 above. The mixing may be performed by kneading the product (particularly the organic acid-modified amorphous starch) with the plasticizer, for example, in a kneading device. The kneading device may include an extruder. For example, the kneading device may be a device having an extrusion function in addition to a kneading function. The product obtained by extrusion using the kneading device may be used as a material for forming a molded body. The product obtained by kneading the amorphous starch modified with the organic acid compound and the plasticizer is particularly suitable as a material for forming a molded body. The product may be subjected to various molding techniques.
[0063] The method for producing a starch-containing material of the present invention may further comprise a step of mixing the product (particularly the amorphous starch modified with an organic acid compound) with a thermoplastic resin. The thermoplastic resin may be as described in 1.4 above. The plasticizer may be further mixed before, during or after the mixing. These mixing processes may be carried out by kneading the amorphous starch modified with an organic acid compound and the thermoplastic resin (and the plasticizer) in, for example, a kneading device. The product obtained by kneading the amorphous starch modified with the organic acid compound and the thermoplastic resin (and the plasticizer) is particularly suitable as a material for forming a molded body. The product may be subjected to various molding techniques.
[0064] 1.7 Application The starch-containing material of the present invention may be used to obtain a molded body. As described above, the molding method for obtaining the molded body may be appropriately selected by a person skilled in the art, and may be, for example, press molding, compression molding, cast molding, vacuum molding, pressure molding, extrusion molding, injection molding, or blow molding.
[0065] The molded body may be, for example, a molded body having transparency. The transparency may mean that, for example, a sheet-like part of the molded body having a thickness of 5 mm or less, particularly 3 mm or less, more particularly about 1 mm, appears to be transparent. For example, it may mean that a molded body having a thickness similar to that of the above-mentioned 5B type dumbbell test piece appears to be transparent. The transparency may be such that, when looking at the main surface of the molded article, the color of an object on the reverse side can be recognized, or it may be more transparent than that (for example, such that a shape or lettering written on an object on the reverse side can be seen).
[0066] Thus, the present invention also provides a molded article formed from the starch-containing material of the present invention. The present invention also provides a method for producing a molded article using the starch-containing material.
[0067] For example, the starch-containing material of the present invention may be used to produce a sheet- or film-shaped molded article, i.e., the present invention also provides a sheet- or film-shaped molded article formed from the starch-containing material of the present invention. The thickness of the sheet- or film-like molded article may be appropriately selected by those skilled in the art, and may be, for example, 10 mm or less, particularly 8 mm or less, and more particularly 5 mm or less. The thickness may for example be 0.1 μm or more, in particular 1 μm or more, more in particular 5 μm or more. The sheet- or film-like molded article may be used in various applications, for example, as a container or packaging. The sheet-like or film-like molded article may be used, for example, in industry, agriculture, forestry, fisheries, or horticulture, and may be used as a material for industrial, agriculture, forestry, fisheries, or horticulture.
[0068] The sheet-like or film-like molded article may be further molded to produce, for example, a container or packaging material having a predetermined shape. The container or packaging material may also be formed directly from the starch-containing material of the present invention without forming a sheet- or film-like molded product. That is, the present invention also provides a container or packaging material formed from the starch-containing material of the present invention. The container or packaging material may be used, for example, as a container or packaging material for food, beverages, medicine, miscellaneous goods, toys, or books, but its uses are not limited to these and it may be used to store or package other items.
[0069] The starch-containing material of the present invention may be used for logistics, storage, or packaging, for example as a cushioning material. The starch-containing material of the present invention may also be used to form kitchenware, e.g., cooking utensils, or tableware, e.g., dishware or cutlery, i.e., the present invention also provides kitchenware or tableware formed from the starch-containing material of the present invention.
[0070] The starch-containing material of the present invention may also be used as a masterbatch. That is, the present invention also provides a masterbatch formed from the starch-containing material of the present invention. The molded article described above may be produced using the masterbatch.
[0071] 2. Method for improving transparency of starch-containing materials for molding
[0072] The present invention provides a method for improving the transparency of a starch-containing material for molding. The method for improving transparency includes producing a starch-containing material for molding using amorphous starch. The amorphous starch is as described in 1.1 above, and the same description also applies to the amorphous starch used in the method for improving transparency. The method for improving transparency may be a method for improving the transmittance over at least the entire wavelength range of 350 nm to 650 nm, for example, a method for improving transparency for increasing the transmittance over at least the entire wavelength range of 350 nm to 650 nm by, for example, 5% or more, preferably 10% or more, more preferably 15% or more. The improvement in transmittance may be, for example, an improvement in transmittance when comparing a case where amorphous starch is used with a case where crystalline starch is used instead of amorphous starch. In one embodiment, the amorphous starch may be an amorphous starch modified with an organic acid compound. The organic acid and the modification with the organic acid are as described in 1.2 above, and the same description also applies to the amorphous starch used in the method for improving transparency.
[0073] The transparency improvement method uses the amorphous starch as one of the raw materials of the starch-containing material for molding. For example, the amorphous starch and a plasticizer may be mixed to produce the starch-containing material for molding. The plasticizer is as described in 1.3 above, and the same description also applies to the plasticizer used in the transparency improvement method of the present invention.
[0074] In one embodiment, in order to produce the starch-containing material for molding, water may be further mixed in addition to the amorphous starch and the plasticizer. In another embodiment, water may not be mixed with the amorphous starch and the plasticizer to produce the starch-containing material for molding.
[0075] In another embodiment, in order to produce the starch-containing material for molding, a thermoplastic resin may be further mixed in addition to the amorphous starch and the plasticizer. The thermoplastic resin is as described in 1.4 above, and the same description also applies to the plasticizer used in the transparency improvement method of the present invention.
[0076] By using the amorphous starch in the transparency improving method of the present invention, an increase in the crystallinity in the starch-containing material for molding can be suppressed. By suppressing the increase in the crystallinity, the physical properties of a molded article produced using the material can be improved, for example, the tensile properties can be improved. That is, the method for improving transparency may be one for suppressing an increase in the degree of crystallinity in the starch-containing material for molding.
[0077] By using the amorphous starch in the transparency improving method of the present invention, it is possible to suppress starch recrystallization when the starch-containing material for molding is molded. The molding may be, for example, a molding technique including heating the material. In the molding, the decrystallized starch may recrystallize. In the transparency improving method of the present invention, the use of the amorphous starch makes it possible to prevent starch recrystallization. That is, the method for improving transparency may be one that suppresses starch recrystallization when the starch-containing material for molding is molded.
[0078] The starch recrystallization may occur, for example, during storage at room temperature of a molded article formed from the material. By applying the transparency improving method of the present invention, the starch recrystallization during storage at room temperature can be prevented. That is, the method for improving transparency may be a method for suppressing starch recrystallization during storage at room temperature of the starch-containing material for molding.
[0079] The transparency improving method of the present invention may be applied, for example, to the production of a molded article formed from a starch-containing material. The starch-containing material may be the starch-containing material described in 1 above, or may be a starch-containing material other than the starch-containing material (i.e., a starch-containing material that does not contain an organic acid). EXAMPLES
[0080] 3. Working Example The present invention will be described in more detail below with reference to examples. Note that the examples described below are representative examples of the present invention, and the scope of the present invention is not limited to these examples.
[0081] 3.1 Tests on combinations of amorphous starch and organic acids
[0082] 3.1.1 Preparation of amorphous starch Crystalline cornstarch (Showa Sangyo Co., Ltd.) was ground using a temperature-controlled milling machine (Micropowder KGW-501, West Co., Ltd.) modified according to the literature (Katsuno, K., Nishioka, A., Koda, T., Miyata, K., Murasawa, G., Nakaura, Y. and Inouchi, N.: Starch / Starke, 62(9), 475(2010), and Murakami, S., Fujita, N., Nakamura, Y., Inouchi, N., Oitome, NF, Koda, T. and Nishioka, A.: Starch, 70(3-4), 1700164(2018)). A schematic diagram of the milling machine is shown in FIG. 1. As shown in the figure, the milling machine 10 is equipped with an upper mill 11 and a lower mill 12. In addition, it is equipped with a heater 13 and a temperature control device 14 for controlling the temperature of these mills. When the raw starch CS to be pulverized is charged, the raw starch CS is pulverized while being heated at a predetermined temperature by the upper mill 11 and the lower mill 12. For the pulverization, the lower mill 12 rotates as shown in the figure. The raw starch CS is subjected to pulverization between the upper mill 11 and the lower mill 12 to obtain amorphous starch ACS. The conditions for the grinding treatment were as follows: Amorphous starch was produced by the grinding treatment. <Crushing processing conditions> Grinding temperature (temperature detected by a thermocouple installed in the mortar): 120℃ Rotation speed (rotation speed of the lower mill. The upper mill is fixed.): 60 rpm Inter-molar distance (clearance between upper and lower mortar): 0 μm Drill groove pitch: Upper and lower dies are both 2.0 mm
[0083] The amorphization of the amorphous starch was confirmed by wide-angle X-ray diffraction measurement, which was performed using a horizontal sample type multipurpose X-ray diffractometer (Ultima IV, manufactured by Rigaku) under the following conditions. <Measurement conditions> Tube current: 40mA Tube voltage: 40kV X-ray source: Cu-Kα ray Scanning speed: 10.0° / min Measurement range: 5°~35°
[0084] The results of the wide-angle X-ray diffraction measurement are shown in FIG. 2. In the figure, A is the measurement result before grinding, and B is the measurement result after grinding. As shown in A of the figure, before grinding, multiple peaks are present, which indicates that the starch is crystalline. On the other hand, after grinding, as shown in B of the figure, the multiple peaks are not present and a gentle curve can be confirmed. In other words, it is clear that the starch is in an amorphized state. In the figure, the vertical axis indicates intensity in arbitrary units, and the measurement results before and after crushing are arranged one above the other only to compare the shapes of the graphs, and do not indicate that the intensity values of these measurement results are increasing.
[0085] 3.1.2 Preparation of citric acid-modified starch and confirmation of modification The crystalline starch (corn starch, hereinafter also referred to as CS) used in 3.1.1 above, the amorphous starch (corn starch, hereinafter also referred to as ACS) produced in 3.1.1 above, and citric acid (hereinafter also referred to as CA, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were prepared. Using these materials, a starch-containing material containing crystalline starch and citric acid, and a starch-containing material containing amorphous starch and citric acid were produced. The production method will be described below with reference to FIG. 3A.
[0086] As shown in the figure, citric acid was dissolved in ethanol (absolute ethanol) to prepare an ethanol solution of citric acid. In preparing the solution, 18 g of citric acid was dissolved in 60 ml of absolute ethanol. The crystalline starch or the amorphous starch was added to the solution, and the mixture was stirred for 24 hours at 80° C. The amount of the crystalline starch or the amorphous starch and the amount of the citric acid added were such that the ratio of citric acid to starch was 60 parts by mass per 100 parts by mass of starch. After the stirring, washing was performed by suction filtration, and the obtained residue was vacuum dried at 50°C for 20 hours using a vacuum dryer (ISUZU SSVK-11S) to obtain citric acid-modified starch. The citric acid-modified starch was a powdery solid. A photograph of the starch prepared as described above is shown in Figure 3B. As shown in the figure, the crystalline starch not modified with citric acid (CS), the amorphous starch not modified with citric acid (ACS), the crystalline starch modified with citric acid (CA-CS), and the amorphous starch modified with citric acid (CA-ACS) were all powdery solids. However, CS and ACS were obtained by vacuum drying the raw material CS and ACS produced from the raw material CS by the above-mentioned grinding method at 50°C for 20 hours using a vacuum dryer (ISUZU SSVK-11S), and the CS and ACS in the following description are those that have undergone this drying process.
[0087] The modification of the starch with citric acid was confirmed by FT-IR measurement using an FT-IR spectrometer (Spectrum 100, manufactured by Perkin-Elmer) under the following measurement conditions. Measurement range: 4000cm -1 ~650cm -1 Measurement method: ATR method Number of scans: 121 1000cm -1 Normalization was performed based on the nearby peak.
[0088] Four types of samples were subjected to the FT-IR measurement: crystalline starch not modified with citric acid (CS), amorphous starch not modified with citric acid (ACS), crystalline starch modified with citric acid (CA-CS), and amorphous starch modified with citric acid (CA-ACS). The FT-IR measurement results of these four samples are shown in FIG. 4. As shown in the figure, the measurement results of CA-CS and CA-ACS show that -1 A peak derived from the carbonyl group (C=O) of citric acid appeared around 1000 nm. This indicates that starch reacted with citric acid in the case of CA-CS and CA-ACS. On the other hand, no such peak was observed in the case of CS and ACS. Thus, it was confirmed that starch was modified with citric acid by the modification treatment using an ethanol solution of citric acid.
[0089] 3.1.3 Preparation and evaluation of thermoplastic starch-containing materials Any of the four types of starch (CS, ACS, CA-CS, and CA-ACS) described above was kneaded with purified glycerin (hereinafter also referred to as Gly, manufactured by Kao) using a kneading device (Labo Plastomill 10c100-01, manufactured by Toyo Seiki Seisakusho Co., Ltd.) to prepare a starch-containing material. The kneading conditions were as follows. Hereinafter, the starch-containing material prepared using CS and Gly will also be referred to as CS / Gly. Similarly, the sample prepared using ACS and Gly, the sample prepared using CA-CS and Gly, and the sample prepared using CA-ACS and Gly will also be referred to as ACS / Gly, CA-CS / Gly, and CA-ACS / Gly, respectively. <Condition> Rotation speed: 20 rpm Temperature: 120℃ Starch and Gly blend ratio: Starch / Gly = 65wt% / 35wt%
[0090] The four kinds of starch-containing materials thus produced were compression molded using a hot press heating machine (mini TEST PRESS10, manufactured by Toyo Seiki Seisakusho) to obtain samples for tensile testing. The shape of the samples was a dumbbell-shaped test piece as shown in FIG. 5. All the numerical values of the dimensions in the figure are in mm. The compression molding conditions were as follows: <Condition> Pressure: 15MPa Time: 10 minutes Temperature: 120℃
[0091] Photographs of the four types of starch-containing materials before and after the compression molding are shown in FIG. As shown in the figure, before the compression molding, CS / Gly and CA-CS / Gly were in a powder form, whereas ACS / Gly and CA-ACS / Gly were in a dough form. Furthermore, neither CS / Gly nor CA-CS / Gly could be compressed to form dumbbell-shaped test pieces, i.e., they were not moldable, whereas ACS / Gly and CA-ACS / Gly could be compressed to form dumbbell-shaped test pieces, i.e., they were moldable. As shown in the figure and in Figure 3B, CS, CA-CS, ACS, and CA-ACS are all powdery solids, but among them, ACS and CA-ACS formed dough-like materials and were moldable when combined with a plasticizer as described above, whereas CS and CA-CS did not become dough-like even when combined with a plasticizer and were not moldable. These results show that starch-containing materials containing amorphous starch can be used as molding materials. Furthermore, since molding was impossible when citric acid was combined with crystalline starch, it is believed that citric acid does not exhibit the effect of improving physical properties when combined with crystalline starch, but exhibits this effect when combined with amorphous starch.
[0092] Amorphous starches are also particularly useful when subjected to a solvent removal process such as the vacuum drying process mentioned above. That is, the solvent removal treatment is very important from the viewpoint of the physical properties (e.g., dimensional stability) of the molded body. However, when the solvent removal treatment was performed in the case where crystalline starch was used, the starch-containing material could not be molded into a test piece, as described above. On the other hand, when amorphous starch was used, the starch-containing material could be molded into a test piece, as described above, even if the solvent removal treatment was performed. Furthermore, when crystalline starch is used and the solvent removal treatment is not carried out sufficiently, although molding is possible, the physical properties of the molded product will be somewhat inferior. Therefore, from the viewpoint of improving the physical properties of the molded body and ensuring moldability, amorphous starch is extremely useful. The water content of the starch-containing material is, for example, less than 5% by the solvent removal treatment (particularly the vacuum drying treatment). That is, the water content of the starch-containing material of the present invention may be, for example, less than 5%. When the water content is in this range, it is considered that the usefulness of amorphous starch is easily exhibited. If the moisture content is 5% or more, recrystallization of starch may proceed, which may result in deterioration of the physical properties of the molded article.
[0093] As described above, in order to obtain citric acid-modified amorphous starch, the solvent is 100% ethanol and does not contain water. This allows the moisture content to be extremely low, which contributes to improving the physical properties of the molded body. Furthermore, by using amorphous starch instead of crystalline starch as the starch component of the starch-containing material in such a low moisture content state, moldability can be ensured. In this way, using a solvent that does not contain water is very useful for obtaining a starch-containing material with excellent physical properties and moldability.
[0094] Next, a tensile test was performed on the dumbbell-shaped test pieces obtained using ACS / Gly and CA-ACS / Gly using a universal testing machine (34SC-1, manufactured by INSTRON) under the following conditions. <Condition> Tensile speed: 10mm / min Chuck distance: 20mm Number of tests: 5
[0095] The results of the tensile test are shown in FIG. 7. The figure also shows a photograph of the dumbbell-shaped test piece that broke as a result of the tensile test. As shown in the figure, CA-ACS / Gly had an improved breaking strain compared to ACS / Gly, that is, it exhibited more ductile fracture behavior. The maximum stress of CA-ACS / Gly was lower than that of ACS / Gly. These results show that the breaking strain can be improved by combining amorphous starch with citric acid. Furthermore, as shown in the photograph in the figure, the transparency of the dumbbell-shaped specimen of CA-ACS / Gly was higher than that of ACS / Gly, which shows that the transparency of the molded body can be increased by combining citric acid with amorphous starch. In this way, the combination of citric acid and amorphous starch can improve the physical properties required for a plastic substitute material.
[0096] The above-mentioned tensile test showed that the tensile properties of the starch-containing material changed. This is believed to be due to the fact that the mobility of the starch molecular chains is improved by modifying the amorphous starch with citric acid. This will be explained with reference to FIG. 8.
[0097] As shown in the upper part of the figure, in the case of ACS / Gly, the hydroxyl groups present in the starch molecular chain form hydrogen bonds. Even if the glycerin is present between the starch molecular chains by kneading ACS / Gly, the affinity with the starch molecular chains is not significantly improved due to the already formed hydrogen bonds. On the other hand, CA-ACS / Gly is citric acid modified, that is, the hydroxyl groups present in the starch molecular chain are replaced by citric acid. This reduces the number of hydrogen bonds between the hydroxyl groups on the starch molecular chain. When CA-ACS / Gly with a reduced number of hydrogen bonds is kneaded, glycerin has excellent affinity with the citric acid substituent, which improves the affinity between the starch molecular chain and glycerin. This is thought to improve the mobility of the starch molecular chain and the tensile properties. Therefore, since organic acids other than citric acid can also substitute hydroxyl groups on starch molecular chains, it is considered that organic acids other than citric acid can also exert a similar effect of improving tensile properties when combined with amorphous starch.
[0098] 3.2 Testing for improving transparency by amorphous starch
[0099] 3.2.1 Preparation of amorphous starch Crystalline cornstarch (Showa Sangyo Co., Ltd.) was ground using the mortar-type grinding device described in 3.1.1 above. The conditions for the grinding were also the same as those described in 3.1.1 above. Amorphous starch was produced by the grinding process.
[0100] The amorphization of the amorphous starch was confirmed by wide-angle X-ray diffraction measurement, which was performed using a horizontal sample type multipurpose X-ray diffractometer (Ultima IV, manufactured by Rigaku) under the following conditions. <Measurement conditions> reflection method X-ray source: Cu-Ka radiation Wavelength: 1.54Å Scanning range: 2θ=5°~35° Scanning speed: 10° / min
[0101] The results of the wide-angle X-ray diffraction measurement are shown in Figure 9. It was confirmed from the figure that the starch was amorphized by the grinding treatment, as described in 3.1.1 above. For example, the amorphization of the starch is confirmed by the absence of peaks in the grey region in the figure. In this figure, the vertical axis also indicates the diffraction intensity in arbitrary units, and the measurement results before and after crushing are arranged one above the other only to compare the shapes of the graphs, and do not indicate that the intensity values of these measurement results are increasing.
[0102] 3.2.2 Preparation and evaluation of starch-containing materials The crystalline starch (corn starch, hereinafter also referred to as CS) used in 3.2.1 above, the amorphous starch (corn starch, hereinafter also referred to as ACS) produced in 3.2.1 above, purified glycerin (hereinafter also referred to as Gly), and distilled water were prepared. Using these materials, a film was produced by kneading and molding. That is, a film formed from a starch-containing material containing crystalline starch and glycerin (hereinafter also referred to as CS / Gly-P), and a film formed from a starch-containing material containing amorphous starch and glycerin (hereinafter also referred to as ACS / Gly-P) were each produced.
[0103] The mixing ratio of the materials in the kneading was 43 parts by mass of Gly and 7 parts by mass of water relative to 100 parts by mass of CS or ACS. The kneading was performed using a kneading device (Labo Plastomill 10c100-01, manufactured by Toyo Seiki Seisakusho) under the following conditions. <Condition> Temperature: 120℃ Rotation speed: 40 rpm Time:3min
[0104] The molding was carried out using a hot press heating machine (MINI TEST PRESS10, manufactured by Toyo Seiki Seisakusho) under the following conditions. <Condition> Temperature: 120℃ Pressure: 15MPa Time: 10 minutes
[0105] The transmittance of the two films (CS / Gly-P and ACS / Gly-P) was measured by UV-visible spectrophotometer (V-630BIO, manufactured by Toyo Seiki Seisakusho) under the following conditions: <Condition> Wavelength: 310~660 nm Reference:Air
[0106] The transmittance measurement results are shown in Figure 10. As shown in the figure, the transmittance of ACS / Gly-P was higher than that of CS / Gly-P over the entire measured wavelength range. These results show that a starch-containing material containing amorphous starch can form a film exhibiting a higher transmittance than a starch-containing material containing crystallized starch. For example, the starch-containing material containing amorphous starch may be a material capable of forming a film having a transmittance of preferably 55% or more, more preferably 60% or more, over the entire wavelength range of 350 nm to 650 nm. Furthermore, by forming a starch-containing material using amorphous starch, the transmittance can be improved over the entire wavelength range of 350 nm to 650 nm. That is, the transparency improving method of the present invention may be a method for improving the transmittance at least over the entire wavelength range of 350 nm to 650 nm. In particular, the transparency improving method of the present invention may be a method for improving the transmittance at least over the entire wavelength range of 350 nm to 650 nm, for example, by 5% or more, preferably 10% or more, and more preferably 15% or more. The improvement in the transmittance may be, for example, an improvement in the transmittance when comparing the case where amorphous starch is used with the case where crystalline starch is used instead of amorphous starch.
[0107] The increase in transmittance due to the use of amorphous starch is believed to be due to a decrease in the crystallinity of the film, in particular due to recrystallization during compression molding. This will be explained below with reference to the results of wide-angle X-ray diffraction measurements, which were performed as described in 3.2.1 above.
[0108] The results of wide-angle X-ray diffraction measurements of crystallized starch before kneading with glycerin (CS), a starch-containing material prepared by kneading crystallized starch, glycerin, and water (CS / Gly), and a film obtained by compression molding the starch-containing material (CS / Gly-P) are shown on the left in FIG. 11. Comparing CS and CS / Gly in the figure, the diffraction peaks derived from amylopectin in crystallized starch decreased when kneaded with glycerin, indicating that the amylopectin became more amorphous when kneaded with glycerin. Next, a comparison of CS / Gly and CS / Gly-P in the figure shows that the diffraction peaks derived from amylopectin increased due to compression molding, indicating that the recrystallization of amylopectin progressed due to compression molding. As described above, it is believed that even if the crystallized starch is decrystallized by kneading with glycerin, it is recrystallized by the subsequent compression molding. The amorphization by kneading and the recrystallization by molding will be described with reference to the schematic diagram on the right side of FIG. As shown in the figure, it is believed that when the molecular chains of crystallized starch are kneaded with water and glycerin, the water and glycerin penetrate between the molecular chains of the starch, and the crystalline parts are changed to amorphous parts. However, it is believed that the water and glycerin in the amorphous parts are released from between the molecular chains by compression molding. In this way, the recrystallization occurs.
[0109] The results of wide-angle X-ray diffraction measurements of amorphous starch before kneading with glycerin (ACS), a starch-containing material prepared by kneading amorphous starch, glycerin, and water (ACS / Gly), and a film obtained by compression molding the starch-containing material (ACS / Gly-P) are shown on the left in FIG. 12. A comparison of ACS and ACS / Gly in the figure shows that the diffraction peak derived from amylopectin did not appear even when amorphous starch was kneaded with glycerin. Next, a comparison of ACS / Gly and ACS / Gly-P in the figure shows that the diffraction peaks derived from amylopectin did not appear even after compression molding, which means that the recrystallization of amylopectin was suppressed during compression molding. As described above, it is believed that when amorphous starch is kneaded with glycerin and then compression molded, the recrystallization of amylopectin can be suppressed more effectively than when crystallized starch is used. The suppression of recrystallization will be described with reference to the schematic diagram on the right side of FIG. As shown in the figure, it is believed that in crystallized starch, the hydroxyl groups between the starch molecular chains form hydrogen bonds. It is believed that the above-mentioned grinding treatment increased the number of hydroxyl groups that can interact with glycerin. It is also believed that the kneading treatment allowed glycerin to penetrate between the molecular chains, and the starch was thermoplasticized solely by glycerin.
[0110] 3.2.3 Effect of storage at room temperature on crystallinity The two types of films, ACS / Gly-P and CS / Gly-P, were stored at room temperature for 14 days, and wide-angle X-ray diffraction measurements were performed as described in 3.2.1 above at the start of storage and on the 3rd, 7th, and 14th days after the start of storage. The measurement results are shown in Figure 13. As shown in the figure, ACS / Gly-P showed less change in crystallinity than CS / Gly-P. From these results, it is believed that the use of amorphous starch can reduce the change in crystallinity that occurs during storage (especially at room temperature). This reduction in change is believed to be due to the inhibition of re-aggregation of amylopectin by the inhibition of evaporation of glycerin.
Claims
1. Amorphous starch, an organic acid, a salt of an organic acid, or both; A starch-containing material comprising:
2. The starch-containing material of claim 1 , wherein the organic acid is a hydroxycarboxylic acid.
3. The starch-containing material of claim 1 , wherein the organic acid has one or more hydroxy groups.
4. The starch-containing material according to claim 1 , wherein the organic acid comprises one or a combination of two or more selected from the group consisting of citric acid, malic acid, tartaric acid, and lactic acid.
5. The starch-containing material according to claim 1 , wherein the amorphous starch has a chemical structure formed by a reaction between a hydroxy group of the amorphous starch and the organic acid or a salt of the organic acid.
6. The starch-containing material according to claim 1 , wherein the starch-containing material is a dried reaction product of the amorphous starch and the organic acid or the salt of the organic acid.
7. The starch-containing material according to claim 1 , wherein the amorphous starch has a crystallinity of 20% or less.
8. The starch-containing material of claim 1 , further comprising one or more components selected from the group consisting of polyhydric alcohols, polysaccharides, and sugars.
9. The starch-containing material according to claim 1 , wherein the starch-containing material comprises one or a combination of two or more selected from the group consisting of glycerin, sorbitol, maltitol and erythritol.
10. The starch-containing material of claim 1 , further comprising a thermoplastic resin.
11. When the starch-containing material was subjected to FT-IR measurement, -1 ~1750cm -1 The starch-containing material according to claim 1, which exhibits a peak at
12. The starch-containing material according to claim 1, which has moldability such that the starch-containing material can be molded into a 5B type dumbbell test piece in accordance with JIS K 7161-2 by hot pressing at 120°C.
13. Providing an amorphous starch; and mixing the amorphous starch with an organic acid, a salt of an organic acid, or both; The present invention relates to a method for producing a starch-containing material containing amorphous starch and an organic acid, a salt of an organic acid, or both of these, comprising the steps of:
14. The method of claim 13, wherein the amorphous starch is contacted with the organic acid, the salt of the organic acid, or both in a solvent.
15. A method for producing a starch-containing material for molding using amorphous starch, A method for improving the transparency of starch-containing materials for molding.
16. The method according to claim 15, which inhibits an increase in crystallinity in the molding starch-containing material.
17. 16. The method of claim 15, wherein the molding starch-containing material inhibits starch recrystallization when molded.
18. The method according to claim 15, which inhibits starch recrystallization during storage at room temperature of the starch-containing material for molding.
Citation Information
Patent Citations
Starch composite material
JP2021187956A